Feminism is queer: the intimate connection between queer and feminist theory - Marinucci, Mimi (Zed Books, 2016)
Feminism is Queer is an introduction to the intimately related disciplines of gender and queer theory. While guiding the reader through complex theory, the author develops the original position of "queer feminism, " which presents queer theory as continuous with feminist theory. While there have been significant conceptual tensions between second wave feminism and traditional lesbian and gay studies, queer theory offers a paradigm for understanding gender, sex, and sexuality that avoids the conflict in order to develop solidarity among those interested in feminist theory and those interested in lesbian and gay rights. This accessible and comprehensive textbook carefully explains nuanced theoretical terminology and includes extensive suggested further reading to provide the reader with a full andthorough understanding of both disciplines.--Publisher information.
Keywords: LGBTQIA2+; approches et analyses; cours; discipline; militance; philosophie; premier cycle; queer; sciences humaines; soc2014; thématiques